The Role of Exploration, Exploitation and Dynamic Capabilities: South Korean Entertainment Firms’ Proactive Response Strategies to the COVID-19 Pandemic - Ahn Yoonha; Shin Hyung-Deok; Hong Saehwa (Economics and Culture, 2025)
This study aims to develop a model of firms’ survival strategy during the COVID-19 pandemic by integrating the concepts of exploration, exploitation, and dynamic capabilities to develop a model of firms’ survival strategy during the COVID-19. We argue that the COVID-19 pandemic forced firms to undergo three processes of sensing, seizing, and reconfiguring suggested by Teece (2007), and to choose exploration or exploitation in each process in a timely manner. The interplay of the three processes for dynamic capabilities and two strategic orientations gives rise to a typology of six proactive response strategies.